Determinants of teacher attrition: Evidence from district-teacher matched data - García, Emma; Han, Eunice S.; Weiss, Elaine (Education Policy Analysis Archives, 2022)
This study examines various factors influencing teacher attrition. Relying on nationally representative, district-teacher matched data, we attempt to identify key determinants of teacher attrition by employing multilevel mixed-effects linear models, which control for commonalities among teachers within the same school district. We find that a stronger teacher voice, a more supportive work environment, fewer school problems, and greater teacher morale significantly reduce teacher attrition. We also show that teacher base salary and returns to experience are negatively associated with teacher attrition. Among all these factors, teacher voice shows one of the largest impacts on teacher attrition, and its effects are much greater for novice teachers than for experienced teachers.